Mechanical behaviors of individual core-shell microspheres and their polymeric composites under different strain rates - Zhang, Xin (2017)
Core-shell microspheres and their polymer composites are widely used in environment and water areas for anticorrosion, self-cleaning, waste absorption, antibacterial and deep sea exploration purposes due to the capability of core-shell structure to carry functional agents. It is also used in aerospace industry and automobile industry due to their lightweight and energy absorption capacities. In order to provide useful information to researchers for optimized design of core-shell microspheres filled polymer composite during application, it is significant to investigate the mechanical response of individual core-shell microsphere and their polymer composite. Core-shell microsphere with void core was firstly investigated. The mechanical properties of Hollow Glass Microspheres (HGM) filled polymers were studied at different strain rates for tensile and compressive behaviors. HGM filled polymers showed strong strain rate effect and the strain rate sensitivity factor increased with the increased strain rate while decreased when filler volume fraction increased. HGM filled polymer absorbed more energy at volume fraction around 7.5% under low strain rate compression. The effect of shell material on the core-shell structures was also investigated. Different shell materials based microcapsules were fabricated through different processes. Quasi-static and dynamic compression setups for individual microcapsule were established. The quasi-static and dynamic properties of individual microcapsule were systematically investigated for the first time. The result indicated that the strength of nickel shell based microcapsules were two orders higher than that of the other two microcapsules at different strain rates. Microcapsule modified epoxy resins were manufactured and evaluated with different weight fractions. The core material may also influence the properties of core-shell structure. Since Shear thickening fluid (STF) can transfer from liquid state to solid state during impact, it can diversify the application of core-shell microspheres. As a result, STF was fabricated and encapsulated successfully by using three different methods for the first time to investigate the influence of core material in a core-shell structure. The mechanical properties of STF capsules were studied to obtain optimized encapsulation process. The introduction of ultraviolet curable resin significantly improved the strength of STF capsule. Repeated loading has been applied on the STF capsules with elastic shell fabricated through a two-step method. The STF capsule using two-step method improved the energy absorption capacity and was reused after each impact. Different deformations and fracture modes of different STF capsules were observed. The importation of STF capsules can improve the impact resistance of silicone gel dramatically since it can improve the energy absorption capacity of matrix material up to 70.16%. Furthermore, the mechanical models of individual microcapsules and their modified polymer composite were studied to further understand their properties. Cowper-Symonds model was employed to predict the strength of microcapsule at specific strain rate. A linear relationship between strain rate and strength was obtained for all the microcapsule modified epoxy resin. The strain rate sensitivity index of nickel shell based microcapsules modified epoxy resin was higher than the other two polymers. A convenient generalized model was proposed to depict the compressive strength of HGM filled polymers. Numerical simulation was employed to study the mechanical modeling of HGM filled polymer by using hexagonal unit cell and periodical boundary condition.